The method for optimizing the placement of compensating and balancing devices in low voltage electrical networks - V. T. Sidorova; S. V. Volkov; A. I. Orlov (Омский научный вестник)
The paper studies the optimization features of low-voltage electrical network modes for energy-efficient power transmission. The main features of these networks are the high values of the zero-sequence voltage unbalance factor and the mismatch of voltage values with the necessary requirements. Therefore, balancing the loads by phases and reactive power compensation are chosen as measures to improve the listed network parameters. One of the main factors for the effective solution of this problem is the determination of load balancing points and reactive power compensation, as well as the required power of the devices used. To solve the multicriteria problem of determining device connection points, an analysis of existing objective functions is carried out. As a result, a target function is proposed that includes costs, voltage losses, zero-sequence voltage asymmetry coefficient. When solving the optimization problem with the help of the proposed objective function, the voltage values and the voltage asymmetry factor at the consumer connection points will be within the required limits. The results of a study of the optimization function using the example of a model network are presented. The calculations are carried out in two stages: the search for sensor's nodes, then their study for optimality. All calculations are carried out in the MATLAB environment, taking into account voltage losses and power.